A Corelation between Poor Motivation and The Efficiency of Female Students in Speaking Skills at Indonesian Islamic Boarding School | 'Alaaqah bayna Dha'f Al-Daafi'iyyah wa Kafaaah Thaalibah fi Mahaarah Al-Kalaam bi Al-Ma'had Al-Islaamiy Al-Induuniisiy - Segaf Baharun; Khonsa' Nabila; Muhammad Sofwan bin Harizan (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
Most demotivating research focuses on the factors of students